Roma Portraits in History Roma Civic Emancipation Elite in Central, South-Eastern and Eastern Europe from the 19th Century until World War II - Marushiakova, Elena; Popov, Vesselin (Brill, 2022)
The book presents the life, visions and activities of the nascent Roma civic elite who initiated the movement for Roma civic emancipation. The book Roma Portraits in History, in the form of individual portraits, presents the life trajectory, visions and specific actions put forward by the nascent Roma elite and its leading representatives concerning the present and future of their community. The book is based on a rich source base of key original archival documents, in multiple languages, including Romani language, discovered in countries across the region of Central, Eastern and South-Eastern Europe, all of which showcase 'Roma elite' visions and action. To fulfil the general picture case studies of representatives from Spain and the US are also included.